Examining the Link Between Teaching Competence and Reading Performance of Grade 6 Learners - Jucil M. Sundo; Rufino T. Tudlasan. Jr. (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This study assessed the status of reading instruction and its relationship to the reading skills of Grade 6 learners of Paknaan Elementary School, Division of Mandaue City, during the School Year 2024 – 2025, as the basis for developing an Enhanced Instructional Reading Guide in Teaching Reading. Specifically, it determined the teachers’ level of teaching competence in terms of content knowledge and pedagogy, learning environment, diversity of learners, curriculum and planning, assessment and reporting, and personal growth and professional development. Likewise, it evaluated the learners’ reading performance in reading fluency, reading comprehension, vocabulary development, and reading engagement, and examined the significant relationship between the two variables. The study employed a descriptive–correlational research design with selected Grade 6 teachers and learners as respondents. Data were collected through validated questionnaires. Findings revealed that the teachers were female, aged 31–40, married, and master’s degree holders with 11–15 years of service. Their teaching competence was rated high, with Curriculum and Planning obtaining the highest mean, while Content Knowledge and Pedagogy ranked lowest. Learners’ reading performance was also high, with Reading Comprehension as the strongest and Reading Fluency as the least developed domain. A very strong positive and significant relationship was found between teachers’ competence and learners’ reading performance. Based on these findings, an Enhanced Instructional Reading Guide was developed to strengthen teachers’ pedagogical competence, promote differentiated instruction, and improve learners’ literacy outcomes.